Relevansi Pembangunan Berkelanjutan dengan Risiko - Dewi , Ratna Ayu Pawestri Kusuma; Robinson , Pardomuan; Puspitarini, Renny Candradewi; Maksin, Mastina; Rizca Yunike Putri; Nuril Hidayati; Deistiara Fitrianti (Universitas Medan Area, 2024)
This research investigates the relevance of development in the city and town of Probolinggo through a quantitative and qualitative approach using development risk analysis. Development risk analysis is used to prove the assumption that the level of social development risk in an area can reflect the level of sustainable development. This research was conducted in Probolinggo City, East Java as one of the areas where development in the fields of tourism, business, and economy is being promoted. The data collection method is carried out by conducting a survey whose results are analyzed to produce the level of development and risk in the development and risk index measure. The research results show that the lower the risk of developing a city in Probolinggo City, the greater the sustainable development achievements in Probolinggo City. These findings can make a significant contribution to the development of regional development policies. The implications of this research can be the basis for developing more effective development strategies by considering social risk factors as the main indicators. This research concludes that the level of economic, social, and ecological risk from the implementation of development in the city of Probolinggo is very low.